Fighting Fungal Threats: Verification of an antifungal susceptibility assay to improve antifungal stewardship in the management of Candida infections - Miss Ashleigh Hale; Miss Disha Lawrence; Mr Adam Pattinson (International Journal of Infectious Diseases)
Introduction: Fungal infections are increasingly acknowledged as a significant public health concern, particularly among immunosuppressed individuals in hospital settings, where an accurate and timely diagnosis is crucial. However, fungal susceptibility tests are primarily offered by external reference laboratories. This requires shipping samples to different locations across the UK, prolonging turnaround times and contributing to delays in appropriate patient management. Methods: To reduce turnaround times, the feasibility of bringing fungal susceptibility testing in-house was explored. The Bruker MICRONAUT-AM antifungal susceptibility assay, which utilises the broth microdilution method, was identified as a promising option for both yeast and cryptococci. Various specimens received in the Microbiology laboratory between August and October 2023, were sent to the reference laboratory for antifungal susceptibility testing and tested in parallel on the MICRONAUT-AM assay. Each sample required one 96-well microtitre plate, which included nine different antifungals in serial dilutions. Minimum inhibitory concentration (MIC) values were recorded at 24-48 hours where growth was monitored using resazurin. Results: In total, 23 fungal isolates identified from a range of patient samples were tested in this verification. However, 4 results were excluded due to lack of comparison data, leaving 19 isolates for analysis. Of these 19, 11 were identified through MALDI-ToF as Candida albicans and 6 as Candida glabrata, with the remainder identified as Candida tropcalis and Candida dublinensis. The reference laboratory provided MIC values and used Clinical and Laboratory Standards Institute (CLSI) breakpoints for interpretation, whereas the MICRONAUT-AM assay interpreted MIC values using the European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints. To enable direct comparison of susceptibility profiles, MIC values from the reference laboratory were reinterpreted using EUCAST breakpoints. Results showed complete concordance, with a 100% match in susceptibility profiles when compared to the reference laboratory results. Discussion: The MICRONAUT-AM assay has been successfully approved for in-house use, specifically for C. albicans and C. glabrata isolates. Verification for the less common Candida species is ongoing. Given the rarity of Cryptococcus isolates, none were included in this study. Comparisons between the performance of the MICRONAUT-AM kit and that of a reference laboratory service confirmed the assay's suitability for clinical implementation. Additionally, the assay's ability to concurrently test nine antifungals on a single ELISA plate offered significant advantages in terms of efficiency and resource optimisation. Conclusion: The main advantage of bringing antifungal susceptibility testing in-house is the reduction in turnaround times. Eliminating the need to send samples to external laboratories streamlines laboratory workflow and removes logistical challenges associated with sample transportation. Financial savings accrued from the in-house testing model will enable resource allocation towards other critical areas. Crucially, processing samples locally will provide clinical teams with susceptibility results sooner, enabling prompt and targeted treatment decisions.